Coping with grief when someone you love dies suddenly - Williams, Mary (Sudden, 2011)
This book is for people who have suffered the shattering experience of a loved one dying suddenly. It aims to help understand the emotions and feelings commonly suffered. It provides straightforward advice on how to cope and who can help you to recover.